Evaluation of Operational Performance of Jawalakhel Roundabout at existing condition and Impact of Geometric Improvement on Its Operational Performance - Karkee, Deepa; Poudel, Reshu; Dhungel, Subash (International Journal on Engineering Technology and Infrastructure Development, 2024)
The study provides an overview of the existing operational performance of Jawalakhel Roundabout with and without cycle lanes in terms of current and future traffic. Jawalakhel is located in the central business district of Lalitpur and connects busy approaches. This connects Pulchowk in the North, Lagankhel in the East, Ekantakuna in the South, and Zoo in the West. It is serving to minimize the resulting conflict between the vehicles; however, due to increasing vehicular movements it is facing challenges like delay, poor level of service and traffic congestion. Video graphic survey method was applied for the collection of traffic volume data and pedestrian volume data during peak hours. The environment and traffic flow parameters are modeled in software 'SIDRA Intersection 8.0'. The calibration and validation of the roundabout model in the software are performed using field data. The performance of the roundabout is assessed based on the LOS, Average Delay, Queue length and is followed by the implementation of the performance enhancement strategies. After analysis, delay; degree of saturation; level of service & 95% of queue vehicles was calculated for existing condition and performance after five years were also analyzed. As a result, the existing performance of the Jawalakhel roundabout was not found to be satisfactory. The result was observed after changing the geometric design of Jawalakhel roundabout.